PENGARUH KOMUNIKASI DAN KONFLIK INTERNAL TERHADAP KINERJA KARYAWAN PT INDUSTRIAL ROBOTIC AUTOMATION SURABAYA - Yuliana Safitri; Rudiatno Rudiatno (Jurnal Ekonomi, Bisnis dan Social, 2024)
This research aims to test and analyze the influence of communication and internal conflict on employee performance. The unit of analysis in this research was 80 people. Samples are taken from the entire population or total sampling. Data analysis was carried out using multiple linear regression using SPSS version 24. Based on the results of data analysis using the t test, it is known that communication and internal conflict partially have a significant effect on employee performance. Meanwhile, based on the results of data analysis using the f test, it is known that communication and internal conflict simultaneously have a significant effect on employee performance. Therefore, it is recommended for companies to pay attention to the communication conditions and internal conflicts of employees so that employee performance is maintained.